(untitled) (International Journal of Engineering and Computer Science, 2017)
As Associate in Nursing rising technology and business paradigm, Cloud Computing has taken business computing by storm. Cloud computing platforms offer straightforward access to a company’s superior computing and storage infrastructure through internet services. We tend to think about the matter of building a secure cloud storage service on high of a public cloud infrastructure wherever the service supplier is not fully trusty by the client. We describe, at a high level, much architecture that combines recent and non-standard science primitives so as to realize our goal. We survey the benefits such Associate in nursing design would offer to both customers and repair suppliers and provide Associate in nursing overview of recent advances in cryptography motivated specifically by cloud storage